ANALISIS DAN PERANCANGAN SISTEM INFORMASI PROMOSI BERBASIS WEB PADA BETACAM STUDIO PHOTOGRAFHY - Emerson, Alex Rei; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2019)
Betacam Studio Photografhy is a studio engaged in photografhy and videografhy, where in general thebusiness process is product production, product promotion, and product sales. The problem experiencedby Betacam Studio Photografhy was that there were still very few people who knew Betacam StudioPhotografhy because its promotion activities were still carried out by distributing brochures and mouthto-mouth promotions so that it was only known around the neighborhood and there was no significantincrease every month. This study aims to analyze and design a promotional information system in theBetacam Studio Photografhy with the prototype method. The solution made by the author is to analyze theold system and design the system offered to be developed using UML. Where researchers combine thefields of marketing science, especially promotion mix with information technology by designingdigitization of product catalogs and promotional brochures with websites as media. This researchproduces a prototype that can be implemented to reach a wider consumer not only limited to theenvironment around Betacam Studio Photografy. This result is expected to be developed into a PromotionInformation System application on Betacam Studio Photografhy.